Benefiting from Energy-Hub Flexibilities to Reinforce Distribution System Resilience : A Pre- and Post-Disaster Management Model - Samadi Gazijahani, Farhad; Salehi, Javad; Shafie-khah, Miadreza (IEEE, 2022)
The proliferation of power-to-gas technology can propound a tailored platform to physically integrate power systems and natural gas grids. These integrated energy systems with different spatial-temporal properties not only could provide significant flexibilities to properly mitigate existing and imminent challenges, but also could increase the robustness of power systems in facing unpredicted conditions. Keeping this in mind, this article outlines a novel conservative two-stage model to improve the resilience of distribution systems against extreme hurricanes. To this end, at the first stage, a pre-disaster scheduling is executed to increase preparedness and robustness of the power system before approaching the tornado. The preparedness index is defined as the sum of energy stored in the electric vehicles and natural gas storages that should be maximized. Subsequently, at the second stage after the recognition of the tornado, some proactive post-disaster actions such as grid partitioning, network reconfiguration, demand-side management, and distributed series reactors are applied to minimize the degradation and vulnerability of the power system. An integrated gas and electricity power flow is proposed in a linear computationally efficient fashion capable of modeling the worst-case scenario. The effectiveness of the model is examined on a distribution grid with multiple energy hubs.
Keywords: Energy hubs (EH); flexibility; integrated energy systems (IES); pre- and post-disaster management; resilience; fi=Sähkötekniikka|en=Electrical Engineering|